Study of diagnostic values of serum thyroid hormone and creatinine in acute renal transplant rejection - Rasool Asoodeh; Mohammad Taghi Shakeri; Habibollah Esmaily; Mehdi Jabbari Noghabi; Razieh Yousefi; Malihe Layeghian (International Archives of Health Sciences, 2018)
Background and Aim: Renal transplantation is one of the main treatments of chronic renal disease that creates a more optimal condition and reduces the risk of fatality. The most common reason behind the functional problems of transplanted kidney in its initial postoperation phase is acute renal transplant rejection, the timely diagnosis of which would help the doctors, begin the required treatments immediately to maintain renal functionality, and prevent further irrecoverable damages. Therefore, identifying the variables which are accurate and reliable predictors of renal transplant rejection can be hugely beneficial. Materials and Methods: In this historical cohort study, 87 nondiabetic patients with renal failure who had received treatments at Kidney Transplantation Department of Imam Reza and Ghaem Hospitals of Mashhad, Iran, were selected and their demographic and clinical characteristics were collected. Among these data, creatinine, fasting blood sugar (FBS) and serum insulin, thyroid-stimulating hormone (TSH), and T3 and T4 hormones were measured four times after the transplant operation. Data were analyzed using SAS 9.3 and MedCalc 13 software. First, the missing data were imputed with appropriate imputation methods, and then using logistic regression and area under receiver operating characteristic (ROC) curve, the most important detectors of acute renal transplant rejection were determined. Significance level (α) was set at 0.01. Results: Using logistic regression analysis and drawing ROC curves for average value of four measurements, the effect of serum creatinine and T4 hormone was found statistically significant (P < 0.01). Conclusion: Results showed that among six variables that were studied (creatinine, FBS, insulin, TSH, T3, and T4), serum creatinine and T4 hormone were statistically significant and also were the most important of acute renal transplant rejection.